Fear of dying and death among nursing students - Gabriela de Almeida Mestre; Ana Carolaine de Souza Batista; Júlia de Souza Soares da Silva; Flávia Emília Cavalcante Valença Fernandes; Wilson Cañon-Montañez; Adriana Elena Hernández-Gamboa; Rudval Souza da Silva (Rev Rene)
Objective: to analyze the fear of the dying process and death among nursing students. Methods: this is an observational, cross-sectional study with a sample of 277 nursing students from the three campuses of a public university, who responded to the Collett-Lester Fear of Death Scale. The Kruskal-Wallis and Mann-Whitney tests were performed. Results: the variables: dying, the death of others and others dying had higher results than the pre-established cut-off point, and the results show that the fear of death varies significantly among nursing students. Conclusion: it was confirmed that fear of the dying process and death varies significantly among nursing students, being influenced by demographic factors and personal experiences such as gender, religion, having or not having children, and the experience of losing a loved one, as well as the current academic semester. Contributions to practice: these findings indicate the importance of literacy in Thanatology in nursing training. Future professionals will face biopsychosocial-spiritual demands inherent to the dying process and death, and constitutes a personal and professional challenge in nursing and healthcare.